2022
DOI: 10.7759/cureus.27706
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hydration Status and Blood Pressure in a Tertiary Care Hospital at Al-Khobar

Abstract: BackgroundHigh blood pressure is a major cardiovascular risk factor. It is a leading cause of increasing morbidity and mortality worldwide. One-third of the adult population worldwide suffers from hypertension. Salt intake, obesity, decreased physical activity, and smoking are well known to increase blood pressure. Fluid retention is the main contributing factor to primary hypertension and adversely affects the cardiovascular system. The emerging evidence suggests a relationship between blood pressure and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, fluid retention is known to have adverse effects on the cardiovascular system independent of blood pressure levels. Mohammedin et al [18] found a strong association between hypertension status and hydration parameters. Hypertensive subjects tended to have a lower percentage of total body water (bioimpedance value) than normotensive subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, fluid retention is known to have adverse effects on the cardiovascular system independent of blood pressure levels. Mohammedin et al [18] found a strong association between hypertension status and hydration parameters. Hypertensive subjects tended to have a lower percentage of total body water (bioimpedance value) than normotensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests an association between blood pressure and hydration status. Fluid retention is a major contributor to essential hypertension and adversely affects the cardiovascular system [17][18][19]. This is of concern as cardiovascular disease is the leading cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, large shifts in ECF volume during aging may decrease R without proportional declines in Xc, resulting in elevated BP at higher PhA. Considering that overall hydration status is known to be positively associated with systemic BP (34), these data may indicate that the relationship between PhA and BP is mediated by an overall increase in TBWa that favors an increase in ICFa over ECFa in young adults, although studies conducted in middle-aged adults have reported in similar fashion (35). Therefore, these findings should only be generalized to young adults at risk of cardiometabolic disease, and it may be possible that the inverse association between PhA and BP reverses throughout the aging process.…”
Section: Discussionmentioning
confidence: 99%